PRIME ALGORITM ON MINIMUM SPANING TREE (Case Study: PDAM Pipe Installation in the Green Palm Resort Makassar) - Side, Syafruddin; Neldi, Neldi (Matematika dan Statistika serta Aplikasinya, 2014)
Graph is one of choice application for the district problem in a true fact of PDAM, Specially at pipe installation problem of PDAM. By this script I will explaint about of Graph Application with the Spanning Tree Minimum with algorithm Prim at pipe installation of PDAM on Green Palm Real Estate Makassar, and determine minimum cost at PDAM Pipe installation. Method of this script is a Survey and investigation Method. The points of spanning tree minimum progressing with Algoritma Prim: (1) T is empty, (2) Put the new minimum capacity (u.v). connect the (u,v) with the new (u,v),and (3) repeat step 2 much as for n-1 times.The points to determine the minimum cost at the pipe installation of PDAM in Green Palm Real Estate Makassar : (1) Design first the graph installation, (2) determine the short paths at the Graph installation to make the minimum cost. By the explaint above, can we concluded if, many side in patent graph can make little capacity of spanning tree minimum and that working. Almost of minimum cost from the survey at pipe installation of PDAM in Green Palm real estate Makassar are, Rp 7.040.000,-. The Graph spanning tree minimum by algorithm Prim also can use to surveying with other spanning tree minimum graph with the other algorithm